Is There Evidence for the Specificity of Closed-Loop Brain Training in the Treatment of Internalizing Disorders? A Systematic Review - Perez, Tyson Michael; Mathew, Jerin; Glue, Paul; Adhia, Divya B.; De Ridder, Dirk (Frontiers in Neuroscience, 2022)
Introduction: Internalizing disorders (IDs, e.g., major depressive disorder, MDD; posttraumatic stress disorder, PTSD; obsessive-compulsive disorder, OCD) are the most prevalent psychopathologies experienced worldwide. Current first-line therapies (i.e., pharmacotherapy and/or psychotherapy) offer high failure rates, limited accessibility, and substantial side-effects. Electroencephalography (EEG) guided closed-loop brain training, also known as EEG-neurofeedback (EEG-NFB), is believed to be a safe and effective alternative, however, there is much debate in the field regarding the existence of specificity (i.e., clinical effects specific to the modulation of the targeted EEG variable(s)). This review was undertaken to determine if there is evidence for EEG-NFB specificity in the treatment of IDs. Methods: We considered only randomized, double-blind, sham-controlled trials. Outcomes of interest included self/parent/teacher reports and clinician ratings of ID-related symptomatology. Results: Of the four reports (total participant no.= 152) meeting our eligibility criteria, three had point estimates suggesting small to moderate effect sizes favouring genuine therapy over sham, however, due to small sample sizes, all 95% confidence intervals (CIs) were wide and spanned the null. The fourth trial had yet to post results as of the submission date of this review. The limited overall number of eligible reports (and participants), large degree of inter-trial heterogeneity, and restricted span of ID populations with published/posted outcome data (i.e., PTSD and OCD) precluded a quantitative synthesis. Discussion: The current literature suggests that EEG-NFB may induce specific effects in the treatment of some forms of IDs, however, the evidence is very limited. Ultimately, more randomized, double-blind, sham-controlled trials encompassing a wider array of ID populations are needed to determine the existence and, if present, degree of EEG-NFB specificity in the treatment of IDs.